5HT2A receptor blockade in dorsomedial striatum reduces repetitive behaviors in BTBR mice. (21st October 2016) - Amodeo, D. A.; Rivera, E.; Cook, E. H.; Sweeney, J. A.; Ragozzino, M. E.
Abstract : Restricted and repetitive behaviors are a defining feature of autism, which can be expressed as a cognitive flexibility deficit or stereotyped, motor behaviors. There is limited knowledge about the underlying neuropathophysiology contributing to these behaviors. Previous findings suggest that central 5HT2A receptor activity is altered in autism, while recent work indicates that systemic 5HT2A receptor antagonist treatment reduces repetitive behaviors in an idiopathic model of autism. 5HT2A receptors are expressed in the orbitofrontal cortex and striatum. These two regions have been shown to be altered in autism. The present study investigated whether 5HT2A receptor blockade in the dorsomedial striatum or orbitofrontal cortex in the BTBR mouse strain, an idiopathic model of autism, affects the phenotype related to restricted and repetitive behaviors. Microinfusion of the 5HT2A receptor antagonist, M100907 into the dorsomedial striatum alleviated a reversal learning impairment and attenuated grooming behavior. M100907 infusion into the orbitofrontal cortex increased perseveration during reversal learning and potentiated grooming. These findings suggest that increased 5HT2A receptor activity in the dorsomedial striatum may contribute to behavioral inflexibility and stereotyped behaviors in the BTBR mouse. 5HT2A receptor signaling in the orbitofrontal cortex may be critical for inhibiting a previously learned response during reversal learning and expression of stereotyped behavior. The present results suggest which brain areas exhibit abnormalities underlying repetitive behaviors in an idiopathic mouse model of autism, as well as which brain areas systemic treatment with M100907 may principally act on in BTBR mice to attenuate repetitive behaviors. Abstract : 5HT2A receptor blockade rescues a reversal learning deficit when injected into the dorsomedial striatum in the BTBR mouse model of autism (e.g. Fig. 2).